Penelitian Pendahuluan Pengolahan Air Limbah Secara Aerobik - Aida Soelaeman (Jurnal Kimia dan Kemasan, 1995)
Aerobic treatment is used for treatment of waste water which is of a relatively low concentration and is in large quantity as well. In this treatment, domestic waste water seeks to purify, by making maximum used of bacteria's ability to take in organic matters. The COD removal from this research are describe that concentration of COD already reached ± 90 %.